2016
DOI: 10.1097/nmd.0000000000000541
|View full text |Cite
|
Sign up to set email alerts
|

Resilience in Patients With Recent Diagnosis of a Schizophrenia Spectrum Disorder

Abstract: This study focused on resilience in patients who recently received a diagnosis of schizophrenia spectrum disorder (SSD). Psychopathological symptoms, depressive symptoms, and hopelessness were considered as sources of stress in the context of psychosis. Forty-eight SSD patients (mean period between diagnosis and recruitment, 20.79 months) were enrolled. Psychopathological symptoms were assessed by the Positive and Negative Syndrome Scale, depression by the Calgary Depression Scale for Schizophrenia, hopelessne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
2
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 62 publications
1
14
2
2
Order By: Relevance
“…Evidence suggests that resilience is higher in healthy individuals when compared to patients. For example, individuals identified as being at clinical high risk (CHR) for psychosis (Marulanda & Addington, ) and individuals with a schizophrenia‐spectrum disorder (Bozikas et al, ) scored significantly lower on self‐report measures of resilience than healthy controls. However, studies which compare resilience in patients and healthy controls often do not account for exposure to risk, an important consideration for resilience research.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence suggests that resilience is higher in healthy individuals when compared to patients. For example, individuals identified as being at clinical high risk (CHR) for psychosis (Marulanda & Addington, ) and individuals with a schizophrenia‐spectrum disorder (Bozikas et al, ) scored significantly lower on self‐report measures of resilience than healthy controls. However, studies which compare resilience in patients and healthy controls often do not account for exposure to risk, an important consideration for resilience research.…”
Section: Introductionmentioning
confidence: 99%
“…Kim et al () identified that resilience was lower in individuals at CHR who ultimately made a transition to frank psychosis than those who did not. Furthermore, in their sample of patients with schizophrenia‐spectrum disorder, Bozikas et al () identified that patients with higher resilience also presented with better functioning. Together, findings like these indicate that higher resilience may have a protective effect against the development, or long‐term effects, of mental illnesses.…”
Section: Introductionmentioning
confidence: 99%
“…Mizuno et al in particular, found that Resilience Scale total scores were significantly lower in patients with schizophrenia and bipolar disorder than in healthy controls, although the difference between patient groups was not significant ( 4 ). A research demonstrated that patients who recently received a diagnosis of schizophrenia spectrum disorder showed less resilience than healthy controls ( 5 ). And patients with chronic non-remitted schizophrenia also showed lower resilience scores than healthy controls ( 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…Resilience is a construct encompassing personal resources and the dynamic process of adaptation to challenging life conditions that could be protective against mental problems (Kim-Cohen, 2007;Rutter, 2006). A few previous studies have shown that low resilience has an effect on depression in patients in various stages of schizophrenia, including those at high risk for psychosis (Bozikas et al, 2016;Marulanda & Addington, 2016;Rossi et al, 2017). Additionally, resilience helps young psychotic patients overcome a major psychosocial obstacle that disrupts their lives (Henderson & Cock, 2015).…”
Section: Resultsmentioning
confidence: 99%